2021
DOI: 10.1371/journal.pone.0256256
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial evaluating the effects of a family-centered HIV care model on viral suppression and retention in care of HIV-positive children in Eswatini

Abstract: Introduction A family-centered care model (FCCM) providing family-based HIV services, rather than separate adult/pediatric services, has been proposed to increase pediatric retention and treatment adherence. Materials and methods Eight health-care facilities in the Hhohho region of Eswatini were randomized to implement FCCM (n = 4) or continue standard-of-care (SOC) separate adult/pediatric clinics (n = 4). HIV-positive children and caregivers were enrolled; caregiver interview and child/caregiver chart abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Nabukeera et al reported a much lower rate of 23% after six months of treatment, which was associated with the WHO clinical stage as well as with ART-induced side effects [20]. Ashburn et al showed that among all children at enrollment, viral suppression and undetectable viral load were 78.4% and 73.9%, respectively, improving to 90.2% and 87.3%, respectively, at 12 months [27]. They showed that the use of a family-based health care system improved adherence and retention in care when compared to having pediatric and adult clinics separated.…”
Section: Discussionmentioning
confidence: 99%
“…Nabukeera et al reported a much lower rate of 23% after six months of treatment, which was associated with the WHO clinical stage as well as with ART-induced side effects [20]. Ashburn et al showed that among all children at enrollment, viral suppression and undetectable viral load were 78.4% and 73.9%, respectively, improving to 90.2% and 87.3%, respectively, at 12 months [27]. They showed that the use of a family-based health care system improved adherence and retention in care when compared to having pediatric and adult clinics separated.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that support from family members played an important role in the successful access to HIV care services by PLHIV and their retention in medical treatment or ART [ 45 47 ]. However, our findings suggest that the role of family members in determining the use of traditional medicines for HIV treatment was a significant barrier to access to HIV care services and the initiation of ART by PLHIV in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature from LMICs highlights caregiver communication as an important factor of treatment across all realms of pediatric care [25][26][27], but many cases of parental dissatisfaction in care and communication remain. Such research has led to the development and application of caregiver-focused care models in some LMICs [28], but one area in which investigation into parental perceptions and preferences is lacking is trauma care.…”
Section: Plos Onementioning
confidence: 99%